2018
DOI: 10.1111/tid.12943
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, risk factors, and outcome of tuberculosis in kidney transplant recipients: A multicentric case‐control study in a low‐endemic area

Abstract: TB in kidney transplant recipients is a rare and late event, but is associated with significantly reduced survival. Our results emphasize the need for systematic screening for LTBI, followed by IPT in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…The symptoms of mycobacterial infections are more insidious compared to those of CAP, and include persistent cough, lymphadenopathy, fever, night sweats, and weight loss. Immunocompromised patients may have only one or a few mild symptoms, such as persistent fever [42], even though dissemination of the organism outside the lungs is common [43]. HRCT findings include miliary nodules, cavitation, centrilobular tree-in-bud nodules, consolidation, mediastinal lymphadenopathy, and pleural effusion [44].…”
Section: Mycobacterial Pneumoniamentioning
confidence: 99%
“…The symptoms of mycobacterial infections are more insidious compared to those of CAP, and include persistent cough, lymphadenopathy, fever, night sweats, and weight loss. Immunocompromised patients may have only one or a few mild symptoms, such as persistent fever [42], even though dissemination of the organism outside the lungs is common [43]. HRCT findings include miliary nodules, cavitation, centrilobular tree-in-bud nodules, consolidation, mediastinal lymphadenopathy, and pleural effusion [44].…”
Section: Mycobacterial Pneumoniamentioning
confidence: 99%
“…Our extensive review of the literature identified four other detailed case reports that documented the development of active TB disease after LTBI treatment . In addition, we found a total of 56/2651 (2.1%) cases of active TB among 41 observational cohorts and six RCT . Among them, only five cases were described in detail.…”
Section: Resultsmentioning
confidence: 95%
“…We found 41 cohort studies that evaluated the outcome of LTBI therapy. Eleven were from Europe, 10 from US and Asia, seven from South America, and one each from Africa, Australia, and Canada . Only nine were prospective .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations